THE DEVELOPMENT OF ELECTRONIC GUIDEBOOK FOR THE IMPLEMENTATION OF PROCUREMENT - Nikijuluw, Vanessa Christina Paskah; Faslah, Roni; Rachmadania, Rizki Firdausi (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2024)
This study aims to produce an e-book guide on the implementation of procurement of goods and services, which helps employees and partner companies understand general provisions such as policies, rights and obligations, sanctions, and the procurement process of goods and services at PT. Pelabuhan Indonesia (Persero). The study uses the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. Based on expert trials, the e-book received an average validity value of 81%, which means "Very Eligible" for use. One-to-one trials through interviews concluded that the guidebook was good. Field test trials received an average value of 84%, which indicates that this e-book is very feasible for use. Overall, the results of all stages of the trial indicate that the development of the e-book guide for procurement of goods and services is good and follows the correct development procedures. This e-book can facilitate learning for employees of PT. Pelabuhan Indonesia (Persero) and partner companies in the procurement process of goods and services.